Probabilities in Experimental Physics: Epistemic Lessons and Challenges - Borrely, Thales; Taschetto, Diana (Intuitio, 2018)
There is one way with which Nature responds to the questions we direct her about the correctness of our understanding of her ways: by means of experiments. In this paper, the pivotal role probability theory plays in experimental physics is presented: it allows us to combine observations that are seemingly analytically incompatible. The main concepts used for such task are introduced and explained. A brief historical sketch of the development of some of such concepts is drawn and it was used as a case-study to defend the position that physics and philosophy are interlinked affairs. Some philosophical consequences of how the intrinsically probabilistic character of experimentation reverberates in our epistemic access of the world are also drawn. ***Probabilidades em Física Experimental: Lições Epistêmicas e Desafios*** É por meio de experimentos que a Natureza responde às questões que a ela direcionamos sobre a adequação de nosso entendimento sobre seu funcionamento. O papel central que a teoria de probabilidades desempenha em física experimental é, neste artigo, apresentada: esta nos permite combinar observações que parecem, em uma primeira leitura, incompatíveis. Os conceitos principais utilizados para fazê-lo são introduzidos e explicados. Uma breve discussão histórica do desenvolvimento de alguns dos mencionados conceitos é indicada e utilizada como estudo de caso para dar suporte à posição que defende que física e filosofia são atividades entrelaçadas. Algumas consequências filosóficas acerca das implicações do caráter intrinsecamente probabilístico da experimentação para o nosso acesso epistêmico do mundo são, também, apresentadas.